Preparation of metal-organic framework polypropylene composites and degradation of printing and dyeing wastewater - SHI Fei; YANG Xue; SU Jing; WANG Hongbo (Gongye shui chuli, 2024)
Metal organic frameworks(MOFs),as non-homogeneous Fenton oxidation catalysts,are difficult to be utilized multiple times and prone to secondary pollution in the treatment of printing and dyeing wastewater. To solve this problem, metal organic framework polypropylene melt blown composites (TA-APTES@MOF@PP) were prepared by modifying the surface of polypropylene melt blown nonwoven (PP) with polyphenol heterogeneous network coating, which resulted in excellent adhesion and secondary reactivity,and by in situ growth of MIL-88B (Fe) crystals on its surface. The catalytic degradation effect and recycling performance of the composites were tested with methylene blue dye (MB) as the target pollutant,and the catalyst delivery ratio and optimal reaction conditions were determined by single-factor optimization. The results showed that the degradation of MB by TA-APTES@MOF@PP (MOF 20 mg) under dark conditions was optimal at 3 h with a degradation rate of 95.3% when the pH of dye solution was 3 and the H2O2 concentration was 50 mmol/L. The composite material has no secondary pollution,easy to recycle, good stability, acid and alkali resistance, catalytic effect in the pH range of 2-11 of dying solution, and the 3 h degradation rate was still above 73.4% after 5 cycles. The composite material had a broad application prospect in printing and dyeing wastewater treatment and water environment management.